Análise de execução dos convênios de melhorias sanitárias domiciliares em municípios do estado de Sergipe - Nascimento, Tatiane Conceição do (2025)
In Brazil, the lack of sanitation infrastructure has been even more critical in small municipalities, especially in the Northeast region. The Home Sanitation Improvement Program, promoted by the National Health Foundation (FUNASA), aimed to provide adequate water and sanitation facilities, contributing to the reduction of waterborne diseases and the improvement of environmental quality. However, the interruption of this program’s implementation in the municipalities of Ribeirópolis/SE and Cedro de São João/SE raised questions about the administrative and structural challenges that hindered its continuity. Given this issue, the present research investigated the factors that led to the cancellation of the Home Sanitation Improvement Program agreements in these municipalities. The study was based on an analysis of the historical and regulatory context of sanitation in Brazil, addressing the National Basic Sanitation Policy and the New Legal Framework for Sanitation. Additionally, it discussed the administrative and operational challenges that affect the execution of such agreements. To address these questions, the research adopted a mixed methodological approach, combining qualitative and quantitative analyses. The investigation was based on documentary research through the analysis of technical reports, official letters, and administrative decisions, with the aim of identifying the obstacles that resulted in the discontinuation of the program in Ribeirópolis/SE and Cedro de São João/SE. The results contributed to a better understanding of the challenges in implementing public sanitation policies and to the development of more effective strategies for promoting health and reducing social inequalities. The research revealed that the implementation of the Home Sanitation Improvement Program (HSIP) in Cedro de São João/SE and Ribeirópolis/SE was hindered by administrative, operational, and financial challenges, leading to the cancellation of the agreements. In Cedro de São João/SE, legal requirements (72%) and insufficient oversight (83%) were the main barriers, while in Ribeirópolis/SE, excessive bureaucracy and lack of oversight negatively impacted the program’s progress. Furthermore, the unequal distribution of beneficiaries and the persistence of inadequate hygiene practices demonstrate the need for complementary environmental health education initiatives. It is concluded that inefficiencies in agreement management and poor oversight were determining factors for the failure to implement sanitation improvements, highlighting the importance of strengthening the technical capacity and administrative structure of municipalities to ensure the effective implementation of public basic sanitation policies.